Delayed-onset adrenal hypoplasia congenita and hypogonadotropic hypogonadism caused by a novel mutation in DAX1. Issue 2 (October 2020) - Liu, Siyue; Yan, Libin; Zhou, Xinrong; Chen, Chen; Wang, Daowen; Yuan, Gang
In this study, we described a male who presented with delayed-onset adrenal hypoplasia congenita (AHC) and mild hypogonadotropic hypogonadism (HHG) without a relevant family history. A novel mutation in the DAX1 (dosage-sensitive sex reversal, congenital adrenal hypoplasia critical region on the X chromosome, gene 1) gene was shown to cause X-linked AHC and HHG. Genetic analysis revealed a novel nonsense mutation, c.154G > T (p.Glu52Term), in the DAX1 gene. Molecular testing demonstrated that the milder phenotype caused by this mutation was due to expression of a partially functional, amino-truncated DAX1 protein generated from an alternate in-frame translation start site (methionine at codon 83). This unusual case revealed a potential mechanism for a novel mutation that resulted in an unusual delayed-onset mild clinical phenotype. It expands the spectrum of adrenal hypoplasia congenita and hypogonadotropic hypogonadism.